Perancangan Interior Children Daycare Kiddy Planets Di Surabaya - Ameilia Harsono (Intra, 2013)
Child is an individual who developing into adults. Within each level of age, the child’s development is also increasing rapidly. Therefore, it is necessary to know the child’s understanding deeper. In modern times, there are many organizations or agencies that put full concentration in children. Due to globalization, the parents have their own busy and in the end they did not have much time for children, so that childrem get less attention. Development of a child is an important part of children’s education. Developing children’s creativity at this age.